2014
DOI: 10.1177/000313481408000122
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Preoperative Cholangitis after Biliary Drainage in Patients who Undergo Pancreaticoduodenectomy on Postoperative Pancreatic Fistula

Abstract: The objective of this study was to examine whether the development of cholangitis after preoperative biliary drainage (PBD) can increase the incidence of postoperative pancreatic fistula (POPF). The study population included 185 consecutive patients who underwent pancreaticoduodenectomy from April 2006 to March 2011. All patients were divided into two groups, which consisted of a “no PBD” group (73 patients) and a PBD group (112 patients). Moreover, the PBD group was divided into a “cholangitis” group (21 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 28 publications
3
15
2
Order By: Relevance
“…This is probably because of pancreatic duct wall inflammation at the site of the future anastomosis and bacterial infection of the bile and pancreatic fluid induced by stenting as has been reported before. 24,25 The result we obtained adds evidence to the hypothesis that pancreatic ductal wall inflammation induced by the pancreatic stent at the site of the future pancreaticoenteral anastomosis may be responsible for POPF and that biliary stent per se does not have any adverse effect at this site. In other words, careful biliary cannulation avoiding repeated inadvertent pancreatic duct cannulation is of utmost importance.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This is probably because of pancreatic duct wall inflammation at the site of the future anastomosis and bacterial infection of the bile and pancreatic fluid induced by stenting as has been reported before. 24,25 The result we obtained adds evidence to the hypothesis that pancreatic ductal wall inflammation induced by the pancreatic stent at the site of the future pancreaticoenteral anastomosis may be responsible for POPF and that biliary stent per se does not have any adverse effect at this site. In other words, careful biliary cannulation avoiding repeated inadvertent pancreatic duct cannulation is of utmost importance.…”
Section: Discussionsupporting
confidence: 62%
“…Stent placement can not only induce pancreatic and bile duct wall inflammation but also introduce infection into the biliopancreatic system, and this may be responsible. 24,25 Does the addition of pancreatic stenting contribute to a higher morbidity after PD than biliary stenting alone? However, the increase in POPF rates after stenting may well be as a result of other confounding factors such as disease stage, pancreatic texture, and ductal diameter.…”
mentioning
confidence: 99%
“…[ 56 ] In another article, univariate and multivariate analyses showed that preoperative cholangitis after PBS and a small pancreatic duct are closely associated with the development of pancreatic fistula. [ 42 ] Although the use of PBS could increase preoperative cholangitis in patients waiting for surgery, there is no clear evidence to support the direct association between PBS and pancreatic fistula. Therefore, the effect of PBS on the occurrence of postoperative pancreatic fistula remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Only patients who belonged to the intermediate‐risk group were included. Patients who were classified as high risk were excluded and routinely received antimicrobial prophylaxis with CZOP until postoperative day 4 . In this study, we always clamped the hepatic duct by clamp forceps to prevent spilling bile juice after resecting the common bile duct.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Sourrouille et al have reported that 5 days of postoperative antimicrobial therapy in patients at high risk of contamination reduces the overall rate of infectious complications after PD. Among patients who underwent PBD, those who had developed cholangitis defined by the Tokyo Guidelines 2007 preoperatively had a particularly high likelihood of developing postoperative infectious complications, and routine use of broad‐spectrum antibiotics as therapeutic antimicrobial therapy has been implicated . Thus, hard evidence as to the duration and selection of antibiotics for use as antimicrobial prophylaxis has been lacking for patients with an intermediate risk for infection, such as those who undergo PD after receiving PBD but have no signs of cholangitis preoperatively.…”
Section: Introductionmentioning
confidence: 99%